Fe-based catalyst for preparing butadiene through dehydrogenation of carbon dioxide oxybutylene and preparation and application of Fe-based catalyst

The preparation of Fe-based catalysts through the channel domain limit strategy solved the problem of easy agglomeration of active components and complex preparation processes, improved the yield and selectivity of 1,3-butadiene of CO2 butene oxide dehydrogenation reaction, and was suitable for industrialization Production.

CN119215969APending Publication Date: 2024-12-31LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411517014.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-31

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-selectivity and high-yield Fe-based catalyst for preparing butadiene through oxidative dehydrogenation of butylene with CO2 and a preparation method of the high-selectivity and high-yield Fe-based catalyst. The catalyst comprises a molecular sieve carrier, an active component iron oxide and an auxiliary metal oxide. The active component and the auxiliary component are confined into abundant pore channels of the molecular sieve by using a pore channel confinement strategy, so that the dispersity of the active component and the auxiliary component is effectively improved, and the active component and the auxiliary component are distributed more uniformly. Meanwhile, through the synergistic effect of multiple components, electron transfer among the components is promoted, and the interaction among metal oxides is enhanced. The prepared catalyst is applied to a reaction for preparing butadiene through CO2 butylene oxide dehydrogenation, and is excellent in catalytic performance and high in butadiene selectivity and yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation of a catalyst for preparing butadiene by dehydrogenating butene through CO2 oxidation, and in particular to a method for preparing a high-selectivity and high-yield Fe-based catalyst. The catalyst is mainly used for preparing 1,3-butadiene by dehydrogenating butene through CO2 oxidation, and belongs to the field of catalysts and engineering technology. Technical Background

[0002] China has an overcapacity in butene production, much of which is burned as fuel, leading to a sharp increase in carbon emissions. Furthermore, CO2 is a major greenhouse gas and a potential underutilized carbon source. Integrating CO2 emission reduction with the n-butene dehydrogenation industry chain not only maximizes the resource utilization of excess n-butene production but also recycles and reuses the emitted CO2, enabling the "green" production of 1,3-butadiene, with promising applications. As an industrial triene, the production capacity and demand for 1,3-butadiene are increasing annually. Butene oxidative dehydrogenation to butadiene is considered a promising technology, currently primarily using oxygen for the production of butadiene. However, oxygen-assisted oxidative dehydrogenation is prone to deep oxidation, and due to the high hotspots in the reaction, a large amount of inert gas is required to minimize safety hazards. Compared to oxygen-assisted oxidative dehydrogenation, CO2-assisted oxidative dehydrogenation can significantly reduce the use of inert gas, improve safety, and reduce the likelihood of accidents. Furthermore, the utilization of CO2 can alleviate the problems of coking and deep oxidation that often occur in oxidative dehydrogenation. In the process described in U.S. Patent 6,958,427, CO₂ is used as a mild oxidant to dehydrogenate ethylbenzene to styrene. Compared to conventional processes, using CO₂ as an oxidant allows for lower operating temperatures and improves reactant conversion and selectivity, while also avoiding the explosion risk associated with oxygen dehydrogenation.

[0003] Currently, the catalysts used for the oxidative dehydrogenation of 1-butene to 1,3-butadiene are primarily iron-based. The lattice oxygen in iron oxides plays a crucial role in the oxidative dehydrogenation reaction. These lattice oxygens oxidize the α-H groups of 1-butene to produce 1,3-butadiene. Therefore, replenishing this consumed lattice oxygen is crucial. However, replenishing lattice oxygen located in a tetrahedral structure is often difficult. Consequently, a growing number of researchers are introducing additives to distort the iron oxide lattice and replenish lattice oxygen, thereby achieving a delicate balance between selective oxidation of butene and activation of carbon dioxide (see "Constructing a high-efficiency iron-based catalyst for carbon dioxide oxidative dehydrogenation of 1-butene: The role of oxygen mobility and proposed reaction mechanism. Appl. Catal. A: General 2019, 572, 71-79"). Molecular sieves have a uniform pore structure with uniform pore diameters and preferentially adsorb polar and unsaturated molecules. Molecular sieve catalysts play a vital role in industrial applications. Molecular sieves also provide a large surface area for the dispersion of active components on the catalyst surface, and their rich pore structure can also limit further aggregation of active components during the reaction process. Furthermore, the unique aluminosilicate structure of molecular sieves can effectively regulate the acidity of the catalyst, thereby changing the adsorption and desorption behavior of reactant and product molecules on the catalyst surface, thereby further improving the catalyst's catalytic performance, including yield and selectivity.

[0004] Patent CN 100428993C discloses a catalyst and preparation method for the dehydrogenation of propane to propylene using carbon dioxide. This patent encapsulates V, Cr, and V-Cr as the primary active components in an SBA-15 molecular sieve, which is then loaded onto FeCrAl alloy sheets. Studies have shown that the catalyst's active components are highly dispersed, resist sintering, and exhibit good thermal stability. However, the catalyst's complex preparation process makes it unsuitable for large-scale industrial production.

[0005] Patent CN 117181283 A discloses a catalyst for the oxidative dehydrogenation of carbon dioxide to produce propylene and its preparation method. This patent utilizes framework-confined immobilization of Pt and Sn onto ERB-1 and MCM-22 molecular sieves. The framework-confined Sn disperses and immobilizes Pt particles, producing uniformly sized, well-dispersed Pt particles. As a result, this catalyst achieves a propane conversion rate of nearly 30% and a propylene selectivity of 90%. However, the use of precious metals as active components increases the overall catalyst cost, making it unsuitable for industrial production.

[0006] The present invention addresses the problems of easy agglomeration of active components, complex preparation process, and low yield and selectivity of 1,3-butadiene in existing CO2 oxidation butene dehydrogenation catalysts for butadiene production. The present invention provides a catalyst with highly dispersed active components, simple preparation process, high yield and selectivity of 1,3-butadiene, and a preparation method thereof. Summary of the Invention

[0007] The present invention provides an Fe-based catalyst for CO2 oxidation of butene and dehydrogenation to butadiene, and a preparation method thereof. The catalyst can not only produce butadiene by CO2 oxidation of butene and dehydrogenation, but also has a high 1,3-butadiene yield and selectivity, a simple preparation process, and is suitable for industrial production.

[0008] The preparation method of the Fe-based catalyst for the dehydrogenation of butene to butadiene by CO2 oxidation of butene according to the present invention comprises the following steps: (1) Sodium metaaluminate, silica sol, and S-1 seed crystals are mixed and crystallized at 150-200°C for 12-72 hours. The obtained product is filtered, washed with water, dried at 80-140°C for 2-12 hours, and calcined at 500-600°C for 4-10 hours to obtain ZSM-5 molecular sieve.

[0009] The mass ratio of each component in terms of oxide is 1.0 SiO2: 0.002~0.5 Al2O3: 0.001~0.3Na2O: 1~30 H2O: 0.01~20 S-1.

[0010] (2) Dissolve the metallic iron salt in anhydrous ethanol, then add the additive precursor salt and stir thoroughly to obtain a uniform solution A.

[0011] The active component precursor salt is at least one of ferric nitrate and ferric acetate. The additive precursor salt is one or more of chromium salts, manganese salts, calcium salts, and potassium salts. The chromium salt is at least one of chromium nitrate and chromium acetate, the manganese salt is at least one of manganese nitrate and manganese acetate, the calcium salt is at least one of calcium nitrate and calcium acetate, and the potassium salt is at least one of potassium chloride and potassium nitrate.

[0012] (3) Immerse the ZSM-5 molecular sieve in solution A so that the liquid level of solution A is just level with the surface of the molecular sieve. Stir thoroughly at 20-60°C for 6-18 hours to form a mixture B. Place the mixture B in a vacuum box at 80-100°C and evacuate at a vacuum degree of 50-80 kPa for 12-48 hours.

[0013] (4) The vacuum-dried block is calcined in an air atmosphere in a muffle furnace at 500-800°C for 2-5 hours, cooled to room temperature, and crushed to obtain an Fe-based catalyst.

[0014] The catalyst prepared by the present invention consists of three parts: a carrier, an active component, and an auxiliary component. The carrier is a ZSM-5 molecular sieve, which accounts for 70% to 90% of the total catalyst mass; the active component is an iron oxide, which accounts for 9% to 25% of the total catalyst mass; and the auxiliary component is at least one of chromium, calcium, manganese, and potassium oxides, which accounts for 1% to 5% of the total catalyst mass.

[0015] The Fe-based catalyst of the present invention is used in the CO2 oxidation of butene to butadiene dehydrogenation reaction. Under the catalysis of the Fe-based catalyst, the reaction is carried out at a space velocity of 4.5 g / (g cat •h), at a reaction temperature of 600°C, 1-butene and a CO2 mixture react to produce butadiene; the volume ratio of 1-butene to CO2 is 1:9; the Fe-based catalyst catalyzes the CO2 oxidation and dehydrogenation of butene to butadiene with high selectivity and high yield, with a butadiene yield of greater than 13% and a selectivity of greater than 23%.

[0016] The specific principles of the present invention are as follows: The present invention adopts a pore confinement strategy to prepare the catalyst. The purpose of vacuum drying during the preparation process is primarily to remove excess gas from the molecular sieve, better confining the active component solution to the molecular sieve's pores. This prevents further agglomeration of the active component and auxiliary component during the calcination process, thereby improving the dispersibility of the active component and auxiliary component. By varying the composition of the active component and auxiliary component, a subtle balance is achieved between the selective oxidation of 1-butene and the activation of carbon dioxide. By adjusting the proportions of each component, the acidity and alkalinity of the catalyst surface are adjusted, thereby optimizing the adsorption and desorption behavior of reactants and products on the catalyst surface, thereby more efficiently and selectively oxidizing 1-butene to the higher-value-added 1,3-butadiene.

[0017] The present invention has the following advantages over the prior art: 1. The active component has a small particle size and high dispersion. In the process of preparing the catalyst by the general impregnation method, it is easy for the active components to aggregate into large particles, which will directly affect the adsorption and desorption behavior of the reactant molecules and product molecules on the catalyst surface, thereby affecting the oxidative dehydrogenation performance. The present invention adopts a pore confinement method to solve this problem. By adopting a vacuum negative pressure method to confine the active components to the mesoporous and microporous structure of the molecular sieve, further growth of nanoparticles during roasting or reaction is avoided. The smaller particle size provides more active sites for the reaction, which facilitates the adsorption and conversion of reactant molecules and active components. At the same time, the smaller particle size reduces the residence time of the product molecules at the active sites, making it easier to desorb at the active sites, thereby avoiding cross-linking of the product molecules at the active sites of the catalyst. While improving the yield, the poisoning effect on the active sites of the catalyst caused by carbon deposition is further reduced.

[0018] 2. Oxygen mobility is strong, and the acid-base sites on the catalyst surface can be controlled. The present invention constructs an iron-based catalyst doped with multiple auxiliary components. Compared with single-component Fe-based catalysts, auxiliary doping distorts the tetrahedral unit cell structure of Fe, making lattice oxygen more easily activated and replenished. At the same time, the interaction between the metals accelerates electron flow, enhancing the redox performance of the catalyst. This makes it easier for the α-H of 1-butene to combine with oxygen molecules to form water, thereby achieving the purpose of oxidative dehydrogenation. In addition, the acidity and alkalinity of the catalyst surface affect the adsorption and conversion behavior of reactant molecules on the catalyst surface and the desorption behavior of product molecules on the catalyst surface. Therefore, suitable acid-base sites are extremely important for improving oxidative dehydrogenation performance. The construction of a multi-component catalyst can more effectively improve the type and abundance of acidic and basic sites on the catalyst surface. The synergistic effect of the active components and auxiliary components can enhance the redox performance of the catalyst and improve the adsorption and desorption behavior of reactant and product molecules on the catalyst surface, thereby improving the selectivity and yield of butadiene.

[0019] 3. The catalyst preparation process is environmentally friendly and simple, making it easy to industrialize. The present invention uses inexpensive metal iron salts as the active component and prepares a catalyst for the dehydrogenation of butene to butadiene by CO2 oxidation through pore confinement and additive doping. Compared to single-component iron-based catalysts using an impregnation method, the catalyst prepared by the present invention can better control the metal dispersion and adjust the acidity and alkalinity of the catalyst surface. The prepared catalyst has high butadiene selectivity and yield, high CO2 utilization, and has broad application prospects. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below with reference to specific examples and comparative examples, but the protection scope of the present invention is not limited to the contents described below.

[0021] Example 1 (1) Sodium aluminate, silica sol (30 wt%), and S-1 seed crystals were mixed to make the oxides of each component in a certain mass ratio of 1.0 SiO2: 0.002 Al2O3: 0.001 Na2O: 1 H2O: 0.01 S-1, and crystallized at 150 ° C for 12 hours. The synthesized product was filtered, washed with water, dried at 80 ° C for 2 hours, and calcined at 500 ° C for 4 hours to obtain ZSM-5 molecular sieve; (2) Dissolve 2.5 g of ferric chloride and 0.3 g of potassium nitrate in 10 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution A; (3) Immerse 10 g of ZSM-5 molecular sieve in solution A until the liquid level of solution A is just level with the surface of the molecular sieve, stir at 20 °C for 6 hours to form mixture B, and place mixture B in a vacuum box at 80 °C and evacuate at a vacuum degree of 50 kPa for 12 hours; (4) The dried block was calcined in a muffle furnace at 500°C for 2 hours under air atmosphere, cooled to room temperature, and crushed to obtain the catalyst; the catalyst was pressed into tablets and sieved to obtain 40-mesh catalyst particles, which were marked as cat-1.

[0022] (5) Catalyst performance evaluation method: A continuous fixed-bed reactor was used to evaluate the catalytic performance of the catalyst for the dehydrogenation of butene to butadiene by oxidation with CO2. 0.1g~5.0g of catalyst and 0.2g~5.1g of quartz sand were loaded into the constant temperature section of the reactor, and then nitrogen was introduced at a ventilation rate of 60 ml / min, and the reactor began to heat up to 600℃. After the fixed bed was heated to 600℃, a mixture of n-butene and CO2 was introduced into the constant temperature section of the fixed bed reactor at a ventilation rate of 60 ml / min in a ratio of 1:9, and the mixture was heated at a ratio of 4.5g / (g cat The catalytic reaction was terminated by passing the reactor at a mass space velocity of 1,3-butadiene (1,3-h) until the product 1,3-butadiene appeared. Reactants and products were analyzed using an online GC9790 Plus gas chromatograph equipped with FID and TCD detectors. The oxidative dehydrogenation performance of the catalyst was evaluated in a continuous fixed-bed reactor using 1-butene as a model reactant. The catalytic performance of catalyst cat-1 is shown in Table 1.

[0023] Example 2 (1) Sodium metaaluminate, silica sol (30 wt%), and S-1 seed crystals were mixed to make the oxides of each component in a certain mass ratio of 1.0 SiO2: 0.01 Al2O3: 0.01 Na2O: 5 H2O: 0.1 S-1, and crystallized at 160 ° C for 16 hours. The synthesized product was filtered, washed with water, dried at 90 ° C for 4 hours, and calcined at 550 ° C for 4 hours to obtain ZSM-5 molecular sieve; (2) Dissolve 2.2 g of ferric chloride and 0.5 g of ammonium metavanadate in 10 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution A; (3) Immerse 10 g of ZSM-5 molecular sieve in solution A so that the liquid level of solution A is just level with the surface of the molecular sieve, stir at 30 °C for 8 hours to form mixture B, and place mixture B in a vacuum box at 85 °C and evacuate at a vacuum degree of 55 kPa for 16 hours; (4) The dried block was calcined at 550°C in an air atmosphere in a muffle furnace for 2 hours, cooled to room temperature, and crushed to obtain the catalyst; the catalyst was pressed into tablets and sieved to obtain 50-mesh catalyst particles, which were marked as cat-2.

[0024] (5) The catalyst performance evaluation method is the same as that in Example 1. The catalytic performance of catalyst cat-2 is shown in Table 1.

[0025] Example 3 (1) Sodium metaaluminate, silica sol (30 wt%), and S-1 seed crystals were mixed to make the oxides of each component in a certain mass ratio of 1.0 SiO2: 0.1 Al2O3: 0.1 Na2O: 8 H2O: 1 S-1, and crystallized at 180 ° C for 18 hours. The synthesized product was filtered, washed with water, dried at 100 ° C for 6 hours, and calcined at 580 ° C for 4 hours to obtain ZSM-5 molecular sieve; (2) Dissolve 2.6 g of ferric chloride, 0.5 g of chromium nitrate, and 0.2 g of potassium chloride in 10 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution A; (3) Immerse 10 g of ZSM-5 molecular sieve in solution A so that the liquid level of solution A is just level with the surface of the molecular sieve, stir at 40 °C for 10 hours to form mixture B, and place mixture B in a vacuum box at 90 °C and evacuate at a vacuum degree of 60 kPa for 24 hours; (4) The dried block was calcined at 580°C in an air atmosphere in a muffle furnace for 2 hours, cooled to room temperature, and crushed to obtain the catalyst; the catalyst was pressed into tablets and sieved to obtain 60-mesh catalyst particles, which were labeled as cat-3.

[0026] (5) The catalyst performance evaluation method is the same as that in Example 1. The catalytic performance of catalyst cat-3 is shown in Table 1.

[0027] Example 4 (1) Sodium metaaluminate, silica sol (30 wt%), and S-1 seed crystals were mixed to make the oxides of each component in a certain mass ratio of 1.0 SiO2: 0.2 Al2O3: 0.15 Na2O: 12 H2O: 5 S-1, and crystallized at 190 ° C for 25 hours. The synthesized product was filtered, washed with water, dried at 110 ° C for 8 hours, and calcined at 600 ° C for 6 hours to obtain ZSM-5 molecular sieve; (2) Dissolve 2.6 g of ferric chloride and 0.6 g of calcium nitrate in 10 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution A; (3) Immerse 10 g of ZSM-5 molecular sieve in solution A so that the liquid level of solution A is just level with the surface of the molecular sieve, stir at 45 °C for 12 hours to form mixture B, and place mixture B in a vacuum box at 100 °C and evacuate at a vacuum degree of 65 kPa for 30 hours; (4) The dried block was calcined in a muffle furnace at 600°C for 3 hours under air atmosphere, cooled to room temperature, and crushed to obtain the catalyst; the catalyst was pressed into tablets and sieved to obtain 70-mesh catalyst particles, which were marked as cat-4.

[0028] (5) The catalyst performance evaluation method is the same as that in Example 1. The catalytic performance of catalyst cat-4 is shown in Table 1.

[0029] Example 5 (1) Sodium metaaluminate, silica sol (30 wt%), and S-1 seed crystals were mixed to make the oxides of each component in a certain mass ratio of 1.0 SiO2: 0.4 Al2O3: 0.2 Na2O: 20 H2O: 10 S-1, and crystallized at 200 ° C for 50 hours. The synthesized product was filtered, washed with water, dried at 120 ° C for 12 hours, and calcined at 600 ° C for 10 hours to obtain ZSM-5 molecular sieve; (2) Dissolve 2.6 g of ferric nitrate and 0.6 g of manganese nitrate in anhydrous ethanol and stir thoroughly to obtain a uniform solution A; (3) Immerse 10 g of ZSM-5 molecular sieve in solution A so that the liquid level of solution A is just level with the surface of the molecular sieve, stir at 50 °C for 16 hours to form mixture B, and place mixture B in a vacuum box at 90 °C and evacuate at a vacuum degree of 70 kPa for 36 hours; (4) The dried block was calcined in a muffle furnace at 600°C for 2 hours under air atmosphere, cooled to room temperature, and crushed to obtain the catalyst; the catalyst was pressed into tablets and sieved to form 80-mesh catalyst particles, which were marked as cat-5.

[0030] (5) The catalyst performance evaluation method is the same as that in Example 1. The catalytic performance of catalyst cat-5 is shown in Table 1.

[0031] Comparative Example 1 (1) Sodium metaaluminate, silica sol (30 wt%), and S-1 seed crystals were mixed to make the oxides of each component in a certain mass ratio of 1.0 SiO2: 0.4 Al2O3: 0.2 Na2O: 20 H2O: 10 S-1, and crystallized at 200 ° C for 50 hours. The synthesized product was filtered, washed with water, dried at 120 ° C for 12 hours, and calcined at 600 ° C for 10 hours to obtain ZSM-5 molecular sieve; (2) Dissolve 3.4 g of ferric chloride in anhydrous ethanol and stir thoroughly to obtain a uniform solution A; (3) Immerse 10 g of ZSM-5 molecular sieve in solution A so that the liquid level of solution A is just level with the surface of the molecular sieve, stir at 60 ° C for 24 hours to form mixture B, and place mixture B in a vacuum box at 80 ° C and evacuate at a vacuum degree of 65 kPa for 44 hours; (4) The dried block was calcined in a muffle furnace at 600°C for 2 hours under air atmosphere, cooled to room temperature, and crushed to obtain the catalyst; the catalyst was pressed into tablets and sieved to form 60-mesh catalyst particles, which were marked as cat-6.

[0032] (5) The catalyst performance evaluation method is the same as that in Example 1. The catalytic performance of catalyst cat-6 is shown in Table 1.

[0033] Comparative Example 2 (1) Sodium metaaluminate, silica sol (30wt%), and S-1 seed crystals were mixed to obtain a certain mass ratio of oxides of each component: 1.0 SiO2: 0.4 Al2O3: 0.2 Na2O: 20 H2O: 10 S-1. Crystallization was carried out at 200℃ for 50 hours. The synthesized product was filtered, washed with water, dried at 120℃ for 12 hours, and calcined at 500℃ for 10 hours to obtain ZSM-5 molecular sieve. 10g of the obtained molecular sieve was placed in water and ultrasonically dispersed to obtain a uniform solution A. (2) Dissolve 3.4 g of ferric chloride, 0.4 g of manganese nitrate, and 0.4 g of chromium nitrate in anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (3) Solution B was slowly poured into solution A and stirred at 60°C for 18 hours to form a mixed solution C; (4) Place the mixed solution C in an oven at 80°C and dry for 48 hours to obtain a block; (5) The dried block was calcined at 580°C in an air atmosphere in a muffle furnace for 2 hours, cooled to room temperature, and crushed to obtain the catalyst; the catalyst was pressed into tablets and sieved to obtain 60-mesh catalyst particles, which were labeled as cat-7.

[0034] (6) The catalyst performance evaluation method is the same as that in Example 1. The catalytic performance of catalyst cat-7 is shown in Table 1.

[0035] Note: The data is for the test reaction temperature of 600 o Test results for the first 20 minutes of time C.

[0036] The results show that, as shown in Table 1, the catalyst prepared using the present invention exhibits superior performance in terms of 1-butene conversion, butadiene yield, and butadiene selectivity (1-butene conversion greater than 80%, butadiene yield greater than 13%, and butadiene selectivity greater than 23%). Compared with the catalyst prepared by the impregnation method, the catalyst prepared using the pore confinement method exhibits superior catalytic performance. Compared with a single Fe / ZSM-5 molecular sieve catalyst, the use of multi-component element doping significantly improves butadiene selectivity, yield, and CO2 utilization. The combination of pore confinement and element doping effectively enhances the catalytic performance of the CO2 oxidation-dehydrogenation of 1-butene to 1,3-butadiene. This demonstrates that the catalyst prepared using the present invention exhibits excellent catalytic performance in the CO2 oxidation-dehydrogenation of butene to butadiene.

Claims

1. A Fe-based catalyst for the dehydrogenation of butene to butadiene by CO2 oxidation, characterized in that: The catalyst is composed of a carrier, an active component and an auxiliary component, wherein the carrier is a ZSM-5 molecular sieve, and the carrier accounts for 70-90% of the total mass of the catalyst; the active component is an iron oxide, and the active component accounts for 9-25% of the total mass of the catalyst; the auxiliary component is at least one of chromium, calcium, manganese, and potassium oxides, and the auxiliary component accounts for 1-5% of the total mass of the catalyst; the preparation method of the catalyst comprises the following steps: (1) Sodium aluminate, silica sol and S-1 seed crystals are mixed and crystallized at 150-200°C. The obtained product is filtered, washed, dried and calcined to obtain ZSM-5 molecular sieve; (2) dissolving the active component precursor salt in anhydrous ethanol, then adding the auxiliary agent precursor salt, and stirring thoroughly to obtain a uniform solution A; (3) Immerse the ZSM-5 molecular sieve in solution A, make the liquid level of solution A just level with the surface of the molecular sieve, stir thoroughly to form mixture B, and place mixture B in a vacuum box to evacuate; (4) The vacuum-dried block is calcined in an air atmosphere in a muffle furnace, cooled to room temperature, and crushed to obtain an Fe-based catalyst.

2. The Fe-based catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (1) of the preparation method, the mass ratio of the components in terms of oxides is 1.0 SiO2: 0.002~0.5 Al2O3: 0.001~0.3 Na2O: 1~30 H2O: 0.01~20 S-1.

3. The Fe-based catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In the preparation method step (1), the crystallization time is 12 to 72 hours; the drying temperature is 80 to 140° C., and the drying time is 2 to 12 hours; the calcination temperature is 500 to 600° C., and the calcination time is 4 to 10 hours.

4. The Fe-based catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (2) of the preparation method, the active component precursor salt is at least one of ferric nitrate and ferric acetate.

5. The Fe-based catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (2) of the preparation method, the auxiliary agent precursor salt is one or more of chromium salts, manganese salts, calcium salts, and potassium salts, wherein the chromium salt is at least one of chromium nitrate and chromium acetate, the manganese salt is at least one of manganese nitrate and manganese acetate, the calcium salt is at least one of calcium nitrate and calcium acetate, and the potassium salt is at least one of potassium chloride and potassium nitrate.

6. The Fe-based catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (3) of the preparation method, sufficient stirring means stirring at 20-60° C. for 6-18 hours.

7. The Fe-based catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (3) of the preparation method, the temperature of the vacuum box is 80-100° C., the vacuum degree is 50-80 kPa, and the vacuuming time is 12-48 hours.

8. The Fe-based catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (4) of the preparation method, the calcination is performed at 500-800° C. for 2-5 hours.

9. Use of the Fe-based catalyst as claimed in claim 1 in the CO2 oxidation of butene by dehydrogenation to butadiene.

10. Use of the Fe-based catalyst as claimed in claim 9 in the CO2 oxidation of butene to butadiene dehydrogenation reaction, characterized in that: Under the catalysis of Fe-based catalyst, 1-butene and CO2 mixed gas react to produce butadiene; the space velocity is 4.5 g / (g cat •h), the reaction temperature is 600℃, and the volume ratio of 1-butene and CO2 mixed gas is 1:9.